Environmental aspects of sustainable agriculture - Myszograj, Sylwia; Płuciennik-Koropczuk, Ewelina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Agricultural policy in the European Union at Community level, as well as in the member states, increasingly emphasises the issue of sustainable agriculture. The pursuit of climate neutrality requires a reduction in emissions from agricultural sources. Above all, it is necessary to fully exploit the potential of agricultural and forestry areas to increase carbon sequestration in biomass and soil, optimise systems for the storage, transport and use of livestock manure, and significantly improve energy efficiency and increase the share of renewable energy in plant and livestock production.
Keywords: climate changes; farm; environmental sustainability; zmiany klimatu; gospodarstwa rolne; zrównoważenie środowiskowe